Pengaruh Debt to Equity Ratio, Debt to Assets Ratio, Net Profit Margin dan Total Assets Turnover terhadap Pertumbuhan Laba - Sheni Victoria; Salza Adzri Arismutia; Ferry Kosadi (Riviera Publishing, 2026)
Profit growth is an important indicator in assessing the financial performance and sustainability of the company, especially in the banking sector which has a strategic role in the economy. Profit fluctuations in banking companies show the need for analysis of financial ratios that can affect profit growth. This research aims to analyze the effect of DER, DAR, NPM, and TATO on profit growth using secondary data obtained from the IDX. The population consists of 47 banking companies officially listed on the IDX during the 2017–2024 period, which was then narrowed down to 19 companies using a non-probability sampling technique with a purposive sampling approach. This study applies a quantitative design combining descriptive and verificative analysis, encompassing classical assumption tests, multiple linear regression, product-moment correlation, and the coefficient of determination. Hypothesis testing was conducted using the T-test to examine partial effects and the F-test to examine simultaneous effects. The results indicate that DER has a positive and significant effect on profit growth (t = 2.346; sig. = 0.020). DAR has a negative and significant effect on profit growth (t = ?3.124; sig. = 0.002). NPM shows no significant effect on profit growth (t = ?1.207; sig. = 0.229). TATO has a negative and significant effect on profit growth (t = ?2.342; sig. = 0.021). Simultaneously, all independent variables significantly influence profit growth with an F-value of 4.570 and a significance of 0.002, which is less than 0.05.